The Influence of Social Media Marketing on Purchase Intention Mediated by Electronic Word of Mouth: a Bibliometric Analysis - Hikmawati, Kuncoro Aprilia; Soetjipto, Budi Eko; Wardhana, Ludi Wishnu (PT. Maju Malaqbi Makkarana, 2025)
This study examines the influence of social media marketing on purchase intention through electronic word of mouth (eWOM). In today's era, eWOM has become one of the key factors influencing consumers